Marketing Mix Untuk Meningkatkan Penjualan Produk Pada Toko Gitar Dimdim Musik Di Baki Sukoharjo - Ridwan Raja Refo; Indah Wahyu Utami; Brillian Nur Diansari (Politeknik Kampar, 2025)
In the current era, the development of the creative music industry in Indonesia is so fast where competition between the creative music industries is getting tougher every day. This does not only apply to large companies, Micro, Small and Medium Enterprises (MSMEs) but also participating in the competition. This study aims to apply the marketing mix to increase sales of Dimdim Musik guitar products in Baki, Sukoharjo. The results of this study are that there are 2 influential variables, namely price variables, promotion variables and 5 variables that not affect product sales, namely place variables, people variables, product variabels, process variabel, physical evidence variabel.